2001
DOI: 10.1006/jsbi.2001.4379
|View full text |Cite
|
Sign up to set email alerts
|

Cryoelectron-Microscopy Image Reconstruction of Symmetry Mismatches in Bacteriophage φ29

Abstract: A method has been developed for three-dimensional image reconstruction of symmetry-mismatched components in tailed phages. Although the method described here addresses the specific case where differing symmetry axes are coincident, the method is more generally applicable, for instance, to the reconstruction of images of viral particles that deviate from icosahedral symmetry. Particles are initially oriented according to their dominant symmetry, thus reducing the search space for determining the orientation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 32 publications
4
110
0
Order By: Relevance
“…By assuming no symmetry in the reconstruction it was observed that there is a fixed orientation between the sixfold tail and the fivefold symmetric head in many tailed phages (14,18,28,29,(38)(39)(40). A reconstruction without assuming any symmetry of the C1 virion showed that the tail consists of an about 250 Å long narrow cylinder, which terminates with a 150 Å long knob, surrounded by a skirt of twelve 180 Å long appendages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By assuming no symmetry in the reconstruction it was observed that there is a fixed orientation between the sixfold tail and the fivefold symmetric head in many tailed phages (14,18,28,29,(38)(39)(40). A reconstruction without assuming any symmetry of the C1 virion showed that the tail consists of an about 250 Å long narrow cylinder, which terminates with a 150 Å long knob, surrounded by a skirt of twelve 180 Å long appendages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Electron micrographs were recorded at a magnification of 33,000 with a CM300 FEG microscope under low-dose conditions. Both mutant virus reconstructions assumed no symmetry and were based on a procedure as described (4,7,34). The N-and C-terminal domains of gp13 were initially fitted manually into the cryoEM density map by using the program Chimera and then optimized with the program EMfit, assuming 2-fold symmetry.…”
Section: Methodsmentioning
confidence: 99%
“…S3). In addition, a hexameric pRNA ring would presumably have six, rather than five, projecting spokes in cryo-EM recon- struction (8). Enforcing sixfold symmetry during reconstruction (8,26) yielded a ring, but without the spokes known to be comprised of P A (3) (approximately 45% of the 120b pRNA mass) due to the imposition of sixfold averaging.…”
Section: Two Flexible Joints and Lack Of Tertiary Interactions In Thementioning
confidence: 99%
“…The requirement of a RNA-ring structure in the assembly and function of the ϕ29 DNA packaging motor contrasts with equivalent motors in other dsDNA phages such as T4, SPP1, lambda, and P22 where protein-protein contacts anchor ring ATPases to the phage proheads (1). Cryoelectron microscopy (cryo-EM) 3D reconstructions (2,3,8) show that pRNA is strategically positioned in the ϕ29 packaging motor to link the capsid, connector and ATPase components of the motor (Fig. 1A).…”
mentioning
confidence: 99%